Process-related factors associated with disciplinary board decisions - Birkeland Søren; Christensen Rene dePont; Damsbo Niels; Kragstrup Jakob (BMC, 2013)
Abstract Background In most health care systems disciplinary boards have been organised in order to process patients' complaints about health professionals. Although, the safe-guarding of the legal rights of the involved parties is a crucial concern, there is limited knowledge about what role the complaint process plays with regard to board decision outcomes. Using complaint cases towards general practitioners, the aim of this study was to identify what process factors are statistically associated with disciplinary actions as seen from the party of the complainant and the defendant general practitioner, respectively. Methods Danish Patient Complaints Board decisions concerning general practitioners completed in 2007 were examined. Information on process factors was extracted from the case files and included complaint delay, complainant's lawyer involvement, the number of general practitioners involved, event duration, expert witness involvement, case management duration and decision outcome (discipline or no discipline). Multiple logistic regression analyses were performed on compound case decisions eventually involving more general practitioners (as seen from the complainant's side) and on separated decisions (as seen from the defendant general practitioner's side). Results From the general practitioner's side, when the number of general practitioners involved in a complaint case increased, odds of being disciplined significantly decreased (OR=0.661 per additional general practitioner involved, p<0.001). Contrarily, from the complainant's side, no association could be detected between complaining against a plurality of general practitioners and the odds of at least one general practitioner being disciplined. From both sides, longer case management duration was associated with higher odds of discipline (OR=1.038 per additional month, p=0.010). No association could be demonstrated with regard to complaint delay, lawyer involvement, event duration, or expert witness involvement. There was lawyer involvement in 5% of cases and expert witness involvement in 92% of cases. The mean complaint delay was 3 months and 18 days and the mean case management duration was 14 months and 7 days. Conclusions Certain complaint process factors might be statistically associated with decision outcomes. However, the impact diverges as seen from the different parties. Future studies are merited in order to uncover the judicial mechanisms lying behind.